THE EFFECT OF PRESENTEISM PERCEPTION ON STRESS AND PERFORMANCE IN HEALTH PERSONNELS: A FIELD RESEARCH - İnci Fatma DOĞAN (Fırat University, 2019)
Presenteism is the feeling that people have to go to work, even though they have discomfort due to emotions, such as heavy workload, fear of losing their jobs, feeling unworthy of themselves, not having the power to make decisions in a matter, and not being able to get support from their manager. Presenteeism is the problem of those who have to work in today’s competitive work environment. As a result of presenteeism that is a consequence of loyalty to work and various workplace and private life pressures, people experience burnout feelings, physical problems, health problems and low performance depending on them and various psychological problems. This situation causes the productivity of both the employee and the working institution to decrease. Presenteism, which drives employees to inefficiency, causes large costs in businesses. Therefore it is necessary to struggle with presenteism, which significantly affects employees' productivity. Stress is another factor that affects the productivity of employees in business life negatively and causes the decrease of the efficiency of the institution and causes the physical and psychological problems of the person. One of the reasons leading to stress is presenteism. Therefore, it may become possible to eliminate the problems that may arise from presenteism as a result of combatting presenteism and a positive contribution will be made to the performances defined as the degree to which people use their potentials and abilities within a certain period of time to achieve their goals. In this study, it was aimed to determine the relationship between sub-dimensions of presenteeism (work-focused presenteeism and psycho-focused presenteeism) and stress and performance. For this purpose, a questionnaire study was carried out in 3 private hospitals operating in the health sector in Adana and the results obtained from the questionnaire were analyzed by SPSS program. In conclusion, as the work focused presenteeism perception of the participants increased, stress levels decreased and their performances increased. Besides, as the psycho-focused presenteism perception increased, the stress level increased and the performance decreased.